PENGARUH PEMBERIAN PAKAN ALAMI KUTU AIR (Daphnia sp) DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN BERAT MUTLAK BENIH IKAN GAPI (Poecilia reticulata) MULAI UMUR 5-45 HARI DI BAK-BAK PERCOBAAN - Muhajir Muhajir; Totok Hariyanto (Universitas Mataram, 2026)
The development of ornamental fish in Indonesia is increasing, especially for freshwater ornamental fish. One of the freshwater ornamental fish that is in great demand by the people today is the guppy fish (Poecilia reticulata). Water fleas (Daphnia sp) is one type of natural food consumed by freshwater fish species. Feeding fish seed is an important factor that must be considered. The purpose of this study was to determine the optimal dose of natural feed Daphnia sp for the absolute growth weight of seeds guppy fish (Poecilia reticulata) within 5 — 45 days. This study used an experimental method with complete random design consist of 5 experiments and 5 repetitions. Treatment A uses a dose of 4%, B; 6%, C ; 8%, D ; 10% and E ; 12%. The test animals were guppy fish seeds from 5-45 days old with an average weight of 0,2 g/tail. The stocking density of guppy is 3 fish/lt and the experimental media used fresh water with a volume of 3 lt/tub. The results showed that experiment C giving the highest average on the growth of guppy weight on the aged of 5-45 days with a height of 0,94 g/tail. The water quality data during the study obtained water temperatures range from 27.2°C – 27.9°C, acidity levels range from 7,3 - 7,8 and dissolved oxygen range from 5,2 - 5,7 ppm.